2021
DOI: 10.1007/s13311-020-00931-5
|View full text |Cite
|
Sign up to set email alerts
|

CREB Participates in Paclitaxel-Induced Neuropathic Pain Genesis Through Transcriptional Activation of Dnmt3a in Primary Sensory Neurons

Abstract: Chemotherapy-induced peripheral neuropathic pain (CIPNP) often occurs in cancer patients treated with antineoplastic drugs. Therapeutic management of CIPNP is very limited, at least in part due to the largely unknown mechanisms that underlie CIPNP genesis. Here, we showed that systemic administration of the chemotherapeutic drug paclitaxel significantly and timedependently increased the levels of cyclic AMP response element-binding protein (CREB) in dorsal root ganglion (DRG) neurons. Blocking this increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 44 publications
(87 reference statements)
2
31
0
Order By: Relevance
“…Consistent with the previous reports [24,25], intraperitoneal (i.p.) injection of paclitaxel, but not vehicle 2, produced dramatic and long-lasting mechanical allodynia, heat hyperalgesia, and cold hyperalgesia on both sides in the vehicle 1-treated mice (Fig.…”
Section: Effects Of Systemic Zl006-05 Administration On the Maintenance Of Paclitaxel-induced Neuropathic Painsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the previous reports [24,25], intraperitoneal (i.p.) injection of paclitaxel, but not vehicle 2, produced dramatic and long-lasting mechanical allodynia, heat hyperalgesia, and cold hyperalgesia on both sides in the vehicle 1-treated mice (Fig.…”
Section: Effects Of Systemic Zl006-05 Administration On the Maintenance Of Paclitaxel-induced Neuropathic Painsupporting
confidence: 93%
“…Paclitaxel-induced neuropathic pain model was carried out according to the protocol previously described [24,25]. Briefly, paclitaxel (4 mg/kg; dissolved in the vehicle) or vehicle (a mixture of ethanol and Cremophor EL (1:1)) was injected intraperitoneally every other day for 4 consecutive days (days 1, 3, 5, and 7; 16 mg/kg in total dose).…”
Section: Animal Modelsmentioning
confidence: 99%
“…C/EBPβ belongs to the C/EBPs family with six members that have been reported, which are basic-leucine zipper transcription factors that interact with CCAAT motifs present in numerous gene promoters. Similar to TFs like myeloid zinc finger [28,29], octamer transcription factor 1 [24,36], and runt-related transcription factor 1 [21], C/EBPβ expression can be regulated following peripheral nerve trauma. A previous study revealed that CCI upregulated C/EBPβ expression at protein and mRNA levels in the ipsilateral L3/4 DRGs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral testing was accomplished by one investigator who was blinded with the group. Five behavioral tests were carried out as described previously, including mechanical, thermal, and cold tests, in addition to locomotor activity and conditional place preference (CPP) tests [25][26][27][28]. Each evoked behavioral test was committed at 30-min intervals.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…All behavioral testing was accomplished by one investigator who was blinded with the group. Five behavioral tests were carried out as described previously, including mechanical, thermal, and cold tests, in addition to locomotor activity and conditional place preference (CPP) tests [18][19][20][21]. Each evoked behavioral test was committed at 30 min intervals.…”
Section: Behavioral Testsmentioning
confidence: 99%